Automated Driving Safer and More Efficient Future Driving - Watzenig, Daniel; Horn, Martin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The main topics of this book include advanced control, cognitive data processing, high performance computing, functional safety, and comprehensive validation. These topics are seen as technological bricks to drive forward automated driving. The current state of the art of automated vehicle research, development and innovation is given. The book also addresses industry-driven roadmaps for major new technology advances as well as collaborative European initiatives supporting the evolvement of automated driving. Various examples highlight the state of development of automated driving as well as the way forward. The book will be of interest to academics and researchers within engineering, graduate students, automotive engineers at OEMs and suppliers, ICT and software engineers, managers, and other decision-makers.
Part 1. Introduction -- 1. Introduction to automated driving -- 2. Privacy and security in autonomous vehicles -- 3. Automated driving from the view of technical standards -- Part 2. The importance of control for automated driving -- 4. Survey on control schemes for automated driving on highways -- 5. Path tracking for automated driving: a tutorial on control system formulations and ongoing research -- 6. Vehicle reference lane calculation for autonomous guidance control -- Part 3. Advances in environment sensing, sensor fusion, and perception -- 7. The role of multi-sensor environmental perception for automated driving -- 8. Galileo-based advanced driver assistance systems - key components and development -- 9. Digital maps for driving assistance systems and autonomous driving -- 10. The history - how it all began - radar sensors in cars -- Part 4. In-vehicle architectures and dependable power computing -- 11. System architecture and safety requirements for automated driving -- 12. Advanced system-level design for automated driving -- 13. Systems engineering and architecting for intelligent autonomous sys-tems -- 14. Open dependable power computing platform for automated driving -- Part 5. Active and functional safety in automated driving -- 15. Active safety towards highly automated driving -- 16. Functional safety of automated driving systems: Does ISO 26262 cover the challenges -- Part 6. Validation and testing of automated driving functions -- 17. The new role of road testing for the safety validation of automated vehicles -- 18. Validation of highly automated safe and secure systems -- 19. Testing and validating tactical behavior planning for automated driving -- 20. Safety performance assessment of assisted and automated driving in traffic: simulation as knowledge synthesis -- 21. From controllability to safety in use - safety assessment of driver assis-tance systems -- 22. Testing autonomous and highly configurable systems - challenges and feasible solutions -- Part 7. A sampling of automated driving research projects and initiatives -- 23. AdaptIVe -- 24. Drive Me -- 25. FUSE -- 26. AutoNet2013 -- 27. ARCHER -- 28. ASSUME -- 29. UFO - Ultraflat overrunable robot for experimental ADAS testing -- 30. ITS Corridor -- 31. European and national initiatives -- 32. ARTEMIS Industrial Association -- 33. ERTRAC -- 34. SafeTRANS -- 35. A3PS.
Keywords: Automotive engineering; Control engineering; Robotics; Automation; Transportation engineering; Traffic engineering; Automotive Engineering; Control, Robotics, Automation; Transportation Technology and Traffic Engineering